Framing Effect, Urutan Informasi dan Keputusan Investasi Deposito Syariah: Studi Eksperimen - Nur Ahmad Ricky Rudianto; Himmatul Ulyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study examines order effect and framing effect on purchasing decisions in deposit planning. This study uses a research method with 2 x 2 factorial research designs between subjects. Participants who are given sequential manipulation of information, good news to bad news, will revise their beliefs for decisions to be taken, compared to participants who are given manipulations consisting of information from bad news to good news. Likewise for the framing effect, participants tend to revise their beliefs for the decisions they will make in the conditions provided that the framing is positive and there is a negative framing effect. For the interaction between the order effect and the framing effect it is proven to give the results of different decisions about reporting that receive information on good news to bad news with positive framing and finance that receives information from bad news to good news with negative framing